Thermally Activated Delayed Fluorescence Materials: Towards Realization of High Efficiency through Strategic Small Molecular Design - Liang, Xiao; Tu, Zhen‐Long; Zheng, You‐Xuan (Chemistry : a European journal, 2019)
Thermally activated delayed fluorescence (TADF) is one of the most intriguing and promising discoveries towards realization of highly‐efficient organic light emitting diodes (OLED) utilizing small molecules as emitters. It has the capability of manifesting all excitons generated during the electroluminescent processes, consequently achieving 100 % of internal quantum efficiency. Since the report of the first efficient OLED based on a TADF small molecule in 2012 by Adachi et al., the quest for optimal TADF materials for OLED application has never stopped. Various TADF molecules bearing different design concepts and strategies have been designed and produced, with the aim to boost the overall performances of corresponding OLEDs. In this minireview, the general principles of TADF molecular design based on three basic categories of TADF species: twisted intramolecular charge transfer (TICT), through‐space charge transfer (TSCT) and multi‐resonance induced TADF (MR‐TADF) are discussed in detail. Several key aspects with respect to each category, as well as some effective methods to enhance the efficiency of TADF materials and corresponding OLEDs from the molecular engineering perspectives, are summarized and discussed to exhibit a general landscape of TADF molecular design to a wide variety of scientific researchers within this particular disciplinary area. Let it shine: A comprehensive review of TADF categories based upon frontier molecular orbit distribution and composition is presented with some general design strategies as well as specific with regard to some unique TADF systems to help realize optimal TADF characteristics. Strategic molecular engineering from device perspective is also illustrated in this Minireview to help researchers better understand and design the ultimately efficient TADF materials.